Adaptation mechanisms of Alcanivorax facilitating its predominance in marine environments - Chen, Zhen; Xiang, Shizheng; Lu, Yao; Lai, Qiliang; Dong, Chunming; Li, Jianyang; Li, Guizhen; Shao, Zongze (Frontiers in Marine Science, 2024)
Alcanivorax, a typical alkane-degrading bacterium, has demonstrated the ability to utilize inorganic electron donor in some reports. However, a comprehensive analysis of its potentiality to utilize inorganic electron donor is still lacking.This study analyzed the metabolic characteristics of 167 Alcanivorax strains , encompassing all 29 recognized species, focusing on the oxidation of inorganic compounds. The sulfur oxidation-related genes sqr and tsdA are prevalent and have various evolutionary origins according to phylogenetic analyses. Potential genes for CO oxidation were present in 39 strains, whereas genes associated with iron, hydrogen, and ammonia oxidation were either rare or absent. The physiological functions of Sqr and TsdA were confirmed in six representative strains under heterotrophic conditions.Adding thiosulfate enhanced Alcanivorax growth, indicating that it could serve as a supplementary energy source. We also demonstrated that Alcanivorax bacteria perform sulfide detoxification through Sqr rather than by gaining energy via sulfide oxidation.Although no strain was confirmed to be chemoautotrophs, we discovered that the two clades, A. xenomutans and A. profundimaris, can grow under conditions with very low organic matter.The ability to utilize inorganic compounds as a supplementary energy source and adapt to car bon oligotrophic growth may contribute to the prevalence of Alcnaiovarax in marine ecosystems.